How do meters mediate? Energy meters, boundary objects and household transitions in Australia and the United Kingdom. (December 2017) - Lovell, Heather; Pullinger, Martin; Webb, Janette
Abstract: This paper investigates the changing role of an integral but often overlooked technology within our energy systems: the meter. Empirical cases from the United Kingdom and Australia demonstrate the repurposing of the energy meter. No longer just an instrument of metrology, the meter is increasingly seen by utilities and governments as a key enabling technology for a raft of objectives, from tariff reform to peak load reduction. We draw on the Science and Technology Studies concept of a boundary object to explore these changes. A boundary object is conceptualised as positioned between different social worlds – such as those of householders, government, and utilities – and as having sufficient interpretive flexibility to mediate between their distinct interests. Here we use the boundary object concept to explain the ways in which the meter is being reconfigured, and in particular to analyse the role of householders in the transition to digital meters.